National Identity as Predicted by Ethnic Identity and Social Distance with Multiculturalism as Mediator: A Study Involving Chinese Indonesian Students in Jakarta - Suryani, Angela Oktavia; Setiadi, Bernadette; Nurrachman, Nani; Panggabean, Hana; Wibawa, Dhevy Setya (Makara Human Behavior Studies in Asia, 2019)
As a large multiethnic country, Indonesia has limited studies regarding factors that may influence the national identity of Indonesians of Chinese descent. This study examined the relations between four variables—ethnic identity, multiculturalism, social distance, and Indonesian national identity—between Chinese (n = 159) and non-Chinese Indonesian university students (n = 158) in Jakarta. A multiple-group path analysis was conducted to analyze data from Chinese and non-Chinese samples. The results revealed that structural covariance invariance was the best fit, describing ethnic identity’s direct prediction of national identity and social distance’s indirect prediction of national identity, fully mediated by multiculturalism. The mean score comparisons showed that both groups exhibited higher national identity than ethnic identity. A context of living in a global urban-metropolitan city may influence identity formation.